2020
DOI: 10.3390/socsci9050077
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Children’s Aspiration Profiles and Self-Efficacy, Life Satisfaction, and Academic Achievement

Abstract: Limited research in the psychology literature has addressed the specifics of children’s future orientations. Using a thematic approach, the present study investigates children’s personal aspirations for their adult lives via a questionnaire that addressed (1) the types of aspiration profiles present in a sample of 456 Italian students aged 8–13 and balanced for gender, and (2) how these profiles differ according to demographics, the number of aspirations, academic and social self-efficacy, life satisfaction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In addition, various successful experiences are accumulated in this process [49]. Similar results were found in a study of 456 Italian students [50]. Therefore, self-efficacy and academic performance reinforce the belief that one is competent in a situation where social and economic constraints are perceived, so that one can pursue a higher social position.…”
Section: The Relationship Of Variables In Terms Of Circumscription and Compromise Theorysupporting
confidence: 56%
“…In addition, various successful experiences are accumulated in this process [49]. Similar results were found in a study of 456 Italian students [50]. Therefore, self-efficacy and academic performance reinforce the belief that one is competent in a situation where social and economic constraints are perceived, so that one can pursue a higher social position.…”
Section: The Relationship Of Variables In Terms Of Circumscription and Compromise Theorysupporting
confidence: 56%
“…Future orientation undergoes development throughout the entire lifespan [3], starting from childhood [13,14] and extending to old age [15]. However, the majority of research on future orientation has focused on adolescents due to their more advanced cognitive abilities compared with children, and their perceived necessity to prepare for adulthood [2].…”
Section: Future Orientation and Adolescencementioning
confidence: 99%
“…Adolescence is a critical period of cognitive, psychological, and physical development, and there is an increased level of stage-salient stress during this phase ( Bergin et al, 2018 ). Several studies have found that life satisfaction is positively related to academic achievement ( Diseth et al, 2012 ; Wong and Siu, 2017 ; Bozzato, 2020 ), whereas adolescents’ life satisfaction also influenced by the use of social media and peer relationships ( Geraee et al, 2019 ; Orben et al, 2019 ). In the findings of a longitudinal study, adolescents who reported positive life satisfaction were at a lower risk of developing external behaviors in stressful events ( Suldo and Huebner, 2004 ).…”
Section: Introductionmentioning
confidence: 99%